Cloud computing based e-government in Iraq using partial least square algorithm - Hayder Salah Hashim; Zainab Amin Al-Sul (Institute of Advanced Engineering and Science, 2021)
The electronic government (e-government) worldwide is slowly progressing. The e-government progress in developing countries, such as Iraq, is slower compared with those of regional countries. Prior research suggested deploying cloud based E-government (CBEG). However, most studies are either review or conceptual. This study aims to examine the CBEG in Iraq and identify the criteria that are required for utilizing this technology. A total of 279 academic staff working in the IT department in Iraqi universities have participated in this study. The findings using matrix and the algorithm of partial least square presented ten criteria. After using the average variance extracted technique, the criteria reduced to seven. Further analysis using smart partial least square was conducted, and this resulted in five important criteria namely, reliability of the service followed by availability, security, trust, and technological competence. Decision makers have to increase the competence of the staff and enhance the CBEG services.